Rock bottom girl - Score, Lucy (Naperville, IL : Bloom Books, 2023)
"Downsized, broke, and dumped, 38-year-old Marley returns to her hometown of Culpepper. Not much has changed. The cool kids are still cool. Now they just own car dealerships and live in McMansions next door. Desperate for a new start, Marley accepts a temporary teaching position. Can she keep the losing-est girls soccer team in school history from killing each other? When the school rumor mill sends Marley to the principal's office to sign an ethics contract, Jake, the tattooed track coach, dog dad, and teacher of the year becomes her new fake boyfriend and alibi - for a price. The deal: he'll teach her how to coach if she teaches him how to be in a relationship. Who knew a fake boyfriend could deliver such real orgasms? Rock bottom can't turn into a foundation for happily ever after. Can it?" --
Keywords: Man-woman relationships -- Fiction; High school teachers -- Fiction; Track and field coaches -- Fiction; Soccer coaches -- Fiction; Romance fiction; Erotic fiction